2022
DOI: 10.1016/j.jhepr.2021.100417
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients receiving palliative chemotherapy for advanced biliary tract cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…After progression to first-line gemcitabine-based chemotherapy, nearly half of the patients are offered second-line chemotherapy. In a retrospective German study, nearly one-third of patients received FOLFOX/CAPOX (capecitabine-oxaliplatin) and less than a tenth was offered FOLFIRI or FOLFIRINOX ( 40 ). Studies that assessed the FOLFIRI regimen in this setting are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…After progression to first-line gemcitabine-based chemotherapy, nearly half of the patients are offered second-line chemotherapy. In a retrospective German study, nearly one-third of patients received FOLFOX/CAPOX (capecitabine-oxaliplatin) and less than a tenth was offered FOLFIRI or FOLFIRINOX ( 40 ). Studies that assessed the FOLFIRI regimen in this setting are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data regarding treatment options beyond 1L and 2L remain scarce [ 18 ]. The ABC-06 trial showed improved OS with modified leucovorin 5-fluorouracil oxaliplatin (FOLFOX) versus best supportive care in patients previously treated with GC [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other analyses have aimed to review outcomes for patients following three lines of palliative systemic therapy; Thol et al determined a mOS1 of 18.2 months for 25 patients treated at a single German centre [26], versus 26.9 months for this population. A further analysis by Rizzo et al, presented in abstract form, found an mOS3 of 4.4 months and mPFS3 of 2.8 months (versus 6.4 and 3.1 months, respectively, for the present population) among 101 patients treated at three academic centres in Italy, with a similarly high proportion of included patients having the iCCA subtype [27]; this study specified chemotherapy as the 3L treatment, and hence, presumably did not include patients treated with targeted therapies, which may explain the differences in survival between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-free interval did not influence inclusion in the present study. Previous analyses, including those mentioned above, have not included data regarding the re-challenge of systemic therapy, reporting proportions of each treatment received in each line but not reporting any relationships between lines of treatment [24,26,29].…”
Section: Discussionmentioning
confidence: 99%